2019
DOI: 10.5334/tohm.442
|View full text |Cite
|
Sign up to set email alerts
|

Merging the Pathophysiology and Pharmacotherapy of Tics

Abstract: Background: Anatomically, cortical-basal ganglia-thalamo-cortical (CBGTC) circuits have an essential role in the expression of tics. At the biochemical level, the proper conveyance of messages through these circuits requires several functionally integrated neurotransmitter systems. In this manuscript, evidence supporting proposed pathophysiological abnormalities, both anatomical and chemical is reviewed. In addition, the results of standard and emerging tic-suppressing therapies affecting nine separate neurotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 135 publications
0
33
0
Order By: Relevance
“…The cerebellum is capable of rapidly modulating basal ganglia activity in real time, leading to more‐precise motor control . This rapid modulation can instead lead to abnormal movements when cerebellar input is abnormal and may explain the roles for the cerebellum in several different motor disorders . Although this report provides additional support for an association between cerebellar pathology and head nodding/complex motor stereotypies, it is recognized that a direct causative effect has not been proven.…”
Section: Case Reportmentioning
confidence: 79%
“…The cerebellum is capable of rapidly modulating basal ganglia activity in real time, leading to more‐precise motor control . This rapid modulation can instead lead to abnormal movements when cerebellar input is abnormal and may explain the roles for the cerebellum in several different motor disorders . Although this report provides additional support for an association between cerebellar pathology and head nodding/complex motor stereotypies, it is recognized that a direct causative effect has not been proven.…”
Section: Case Reportmentioning
confidence: 79%
“…Lastly, there are those investigatorsincluding the authors-who have suggested that a disruption in multiple sites within the CBGTC circuit, or brain region inputting to the circuit, could lead to an aberrant message arriving at the primary motor cortex, thereby enabling the tic. Because several recent reviews [67][68][69] have extensively presented available clinical and animal model investigative data, only a more general overview is provided.…”
Section: The Contemporary Versionmentioning
confidence: 99%
“…Recognizing the extensive data set for multiple transmitters, the identification of new complex synaptic chemical interactions, and our current space restrictions, the interested reader is referred to several recent reviews. [65][66][67] In the following sections, we focus on several specific transmitters and recent findings in animal models. One important takehome message is to recognize the significant interaction that exists among various neurotransmitters (Figure 3).…”
Section: -Lyman Beechermentioning
confidence: 99%
See 1 more Smart Citation
“…Tourette syndrome (TS) is a complicated neuropsychiatric syndrome whose primary symptoms include chronic motor and vocal tics (1,2). Tics are defined as quick, rapid, recurrent, nonrhythmic, brief movements, or vocalizations with a waxing and waning course (3). TS is considered a complicated sensorimotor syndrome rather than a purely motor disease.…”
Section: Introductionmentioning
confidence: 99%